Effect of defects in adhesive layer on the interfacial bond behaviors of externally bonded CFRP-to-concrete joints. (1st March 2023) - Li, Peng-Da; Zhao, Yao; Wu, Yu-Fei; Lin, Jian-Ping
Highlights: An experimental study on the influence of interface defects on FRP-concrete interface bonding behavior is designed. Based on the digital image correlation (DIC) technique, the effects of defect size, shape and location on the FRP interfacial bonding behavior were investigated. When the defect area is less than 5%, the reduction of debonding load is similar to the fluctuation amplitude in the conventional interface debonding process, and the effect of defects is limited and can be ignored. Based on the in-depth analysis of experimental data, a bond strength degradation model considering FRP-concrete interface defects is established. Abstract: The structural strengthening technique using fiber-reinforced polymer (FRP) composites to strengthen concrete structures has been widely used. For this reinforcement technique, the stress transfer mechanism at the FRP-concrete interface is one of the key factors affecting the reinforcement effectiveness. In practice, the bond layer is prone to defects due to uneven concrete surface, environmental deterioration or external loading during service life, which can weaken the bonding performance of the FRP-concrete system and even lead to unexpected structural failure in severe cases. In this paper, an experimental study on the influence of interface defects on FRP-concrete interface bonding behavior is designed. Based on the digital image correlation (DIC) technique, the effects of defect size, shape and location on the FRP interfacial bonding behavior were investigated separately. It was found that when the defect area was less than 5% of the effective bond area, the reduction of debonding load was similar to the fluctuation of the conventional interfacial debonding process, and the effect of defects on the interfacial bonding performance was relatively limited. The results also show that the degree of influence of defects on bonding performance varies for different configurations. The higher the concentration of defects, the higher the decrease in the FRP-concrete bearing capacity, especially those defects closer to the FRP boundary. Meanwhile, the proposed loading capacity reduction model considering the defect area is compared with the experimental results to assess the severity degree of defects.